2021
DOI: 10.48550/arxiv.2103.15643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Twisted Spectral Triples without the First-Order Condition

Pierre Martinetti,
Jacopo Zanchettin

Abstract: We extend twisted inner fluctuations to twisted spectral triples that do not meet the twisted first order condition, following what has been done in [6] for the non twisted case. We find a similar non-linear term in the fluctuation, and work out the twisted version of the semi-group of inner perturbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…(3.1), replacing the commutator for a twisted one [20]. In addition, if the twisted first-order condition does not hold, one should add a nonlinear term [13,22]. We thus consider the twisted-covariant Dirac operator…”
Section: B Grading and Real Structurementioning
confidence: 99%
See 2 more Smart Citations
“…(3.1), replacing the commutator for a twisted one [20]. In addition, if the twisted first-order condition does not hold, one should add a nonlinear term [13,22]. We thus consider the twisted-covariant Dirac operator…”
Section: B Grading and Real Structurementioning
confidence: 99%
“…To guarantee that the twisted covariant operator (3.28) is self-adjoint, one assumes that the twisted 1-form A ð1Þ is self-adjoint (Proposition 3.8 in Ref. [22]) (actually, this is not a necessary condition, but requiring A ð1Þ to be selfadjoint makes sense viewing the fluctuation D → D A as a three-step process…”
Section: B Grading and Real Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it becomes relevant to extend to the twisted case the results of [14] regarding inner fluctuations without the first-order condition. This has been done in [49], where it was shown that the removal of the twisted first-order condition yields a second order term in the twisted fluctuation (38), which is a straightforward adaptation of the term worked out in the non-twisted case.…”
Section: Twisted Fluctuation Without the First-order Conditionmentioning
confidence: 99%
“…Hence the necessity to adapt to the twisted case the fluctuations without first-order condition introduced in [14]. This has been done in [49] and is summarised in section 4.3.…”
Section: Introductionmentioning
confidence: 99%